Corresponding Associations: the Poetics and Limits of Photography as Dialogue. (3rd July 2019) - Palmer, Daniel
Abstract: Over the past decade, an increasing number of artists have engaged in photographic projects involving image-based dialogue. These invariably take the form of back-and-forth exchanges of photographs, animated over extended periods of time and often across continents. The immediate context for these dialogues is networked photography – photo-messaging and social media – that also enables people to share photographs in a conversational manner. This article explores a variety of artist-led photographic exchange and correspondence projects and proposes that such experiments reveal a number of distinctive qualities about photographs taken in response to an image made by another, and in anticipation of a visual response. The article concludes by probing the parameters and limits of photo-dialogues for both artists and viewers.